2022
DOI: 10.3390/microorganisms10091764
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Probiotics on COVID-19 Infection by Targeting the Gut–Lung Axis Microbial Cross-Talk

Abstract: The ecosystem of the human gastrointestinal tract, named gut microbiota, represents the most thoroughly mapped ecosystem. Perturbations on bacterial populations cause dysbiosis, a condition correlated to a wide range of autoimmune, neurological, metabolic, cardiovascular, and respiratory diseases. The lungs have their flora, which are directly related to the gut flora via bidirectional communication allowing the transport of microbial metabolites and toxins produced by intestinal bacteria through the circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…For ages 85 and older, probiotic administration increased IgA antibody levels. Synodinou et al ( 18 ) believed that probiotics acted by blocking the virus from invading and proliferating in host cells, by stimulating the immune response, and by suppressing the activation of NLRP3 inflammasome. Moreover, Anwar et al ( 44 ) suggested that probiotic metabolites might have antiviral effects on COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For ages 85 and older, probiotic administration increased IgA antibody levels. Synodinou et al ( 18 ) believed that probiotics acted by blocking the virus from invading and proliferating in host cells, by stimulating the immune response, and by suppressing the activation of NLRP3 inflammasome. Moreover, Anwar et al ( 44 ) suggested that probiotic metabolites might have antiviral effects on COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For influenza viruses, probiotics can activate human and cellular immune responses to increase IFN- γ and IL-2, thereby increasing the host's resistance to influenza virus infection. Many researchers believe that probiotics may have a potential effects on patients with COVID-19 ( 4 , 17 , 18 ). However, there is still a lack of reliable research evidence on the impact of probiotics for COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The human gut microbiota plays an important role in resisting viral infection. Changes in the abundance of gut microbiota or the concentration of its metabolites can cause immune disorders, and viruses can also regulate the homeostasis of the immune system 78–80 …”
Section: Dynamic Changes Of Microbiota In Covid‐19mentioning
confidence: 99%
“…Therefore, blocking NLRP3 pathway is considered feasible in drug therapy to attenuate cytokine release in patients ( 52 ). Probiotics can also be suppressed the NLRP3 inflammasome without affecting normal immune function ( 53 ).…”
Section: Innate Immune Systemmentioning
confidence: 99%